Runoff estimation for the Karjan river basin using NRCS CN method - Dr. K. N. Sondarva; SHRIVASTAVA, P.K.; JAYSWAL, P.S.; PATEL, V.A. (Journal of Soil and Water Conservation, 2026)
Karjan river basin falls in the Narmada, Vadodara, Surat district of the Gujarat state, India in which the major part of watershed is covered by Narmada district which is situated in the Southern part of the Gujarat state. Its catchment area is about 1538.38 km2. The area having Rajpipla hills, which is merging with the Saputara and Shyadri ranges. NRCS CN method was adopted for the estimation of runoff for year 1999 to 2021. It was found that the highest runoff was observed in the year of 2020 as 842.11 mm and the lowest runoff was observed in the year of 2016 as 57.85 mm. The highest rainfall contribution to runoff was observed in the year of 2020 as 40.29 percent and the lowest contribution of rainfall to runoff was observed in the year of 2016 as 7.25 percent. The value of the RSR was found to be 0.536 which is under category of good model performance, similarly percent of bias (%) was found to be -0.489 which is under very good model performance category and Nash-Sutclife model efficiency (NSE) values were found to be 0.781 under very good model performance. The coefficient of determination (R2) is obtained from the regression analysis (scattered plot) of the observed runoff values (mm) and estimated runoff value (mm) as shown in Fig. 4.26, and it was found 0.816 which shows good correlation between observed and estimated values of runoff for the year 1999 to 2021.